Misleading Presentation of Colorectal Cancer in an Otherwise Healthy Patient - Aljarshawi, Mustafa; Albadree, Haitham; Bahar, Hasan; Al-Imam, Ahmed (Journal of the Faculty of Medicine Baghdad, 2021)
Background: Colorectal cancer (CRC) represents the second most common malignancy and the fourth most common cause of cancer deaths. CRC can manifest early with bright red bleeding per rectum, tenesmus, and altered bowel habits. These symptoms are often attributed to benign lesions, including anal fissure. Our objective is to highlight the alarming scenario of an anal fissure masking the clinical features of an underlying colorectal cancer in healthy middle-aged patients. Case Report Our case report aims to discuss how congruent clinical features of benign-looking anal fissure can delay the diagnosis of rectal cancer. In January 2019, a healthy forty-four years old Iraqi male with no family history of colorectal neoplasms presented to Baghdad Medical City. He suffered from a long-standing peri-anal pain and infrequent bowel motion that was initially diagnosed as an anal fissure. Subsequent clinical assessment, with endoscopy, confirmed the presence of colorectal adenocarcinoma. We also carried out analytics, using Google Trends, to assess the spatiotemporal mapping of web users interested in case scenarios similar to our patient. Conclusion Anal fissure could coexist with colorectal cancer, even in younger patients. Therefore, it is essential to consider anal fissure and colorectal cancer on clinical assessment. Follow-up visits are paramount to exclude underlying life-threatening aetiology at secondary care.